Busy Book for Improving Students' Language Skills - Nuriani Nuriani; Juli Juli (STAI Miftahul Ula Nganjuk, 2023)
Education for early childhood is a very important educational stage for a child because various developments are taking place, including language development. To optimize children's language development, appropriate learning media is needed, one of which is the busy book. This is a qualitative descriptive research doing library research which aims to describe busy books as learning media to stimulate early childhood language skills. In this study, writer collected data from various research journals and books related to busy books and early childhood education. Research results from various journals show that busy books can stimulate children to recognize symbols and letter sounds, assemble letters into words, and assemble words into meaningful sentences; activities in the busy book can improve speaking skills by mentioning and telling the pictures in the busy book. This study shows that busy books can be used as learning media to stimulate early childhood language skills.